1999
DOI: 10.1002/(sici)1096-8628(19991215)88:6<676::aid-ajmg18>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies of D2 and D4 receptor genes and alcoholism

Abstract: The purpose of the present study was to evaluate two polymorphisms near the D2 receptor gene (TaqI A RFLP and C microsatellite) and a VNTR for D4. A nonparametric linkage (NPL) technique, SIBPAL, was used to test for the presence or absence of linkage in 54 multiplex alcoholic families. These families had been ascertained through two alcoholic proband siblings in order to increase the density of alcoholic cases within these pedigrees. Phenotypic definitions of alcoholism were manipulated in an effort to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 65 publications
(76 reference statements)
0
22
0
1
Order By: Relevance
“…Two studies have found evidence for linkage in a region containing the D4 receptor polymorphism [Long et al, 1998;Hill et al, 1999a]. Long et al reported a LOD score of 2.11, P = 0.00007 for D11S1984.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have found evidence for linkage in a region containing the D4 receptor polymorphism [Long et al, 1998;Hill et al, 1999a]. Long et al reported a LOD score of 2.11, P = 0.00007 for D11S1984.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported from four previous studies of affected family-based samples (Bolos et al, 1990;Edenberg et al, 1998;Neiswanger et al, 1995;Parsian et al, 1991). Increased rates of allele sharing for the TaqI polymorphism have, however, been reported from two sibpair linkage studies (Cook et al, 1996;Hill et al, 1999), although this findings was not replicated in another study . Taken together, our results are congruent with the notion that the A1 allele is not a generalized risk factor for alcohol abuse and dependence symptoms in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Our most recent PubMed search found > 3400 published reports on the subject. The A1 allele of the DRD2 gene, Taq1 A1 allele, may also be involved in comorbid antisocial personality disorder symptoms, 52 high novelty seeking, 53ā€“56 alcoholism, 37 and addictive behaviors. 20,33 Addictions are increasingly recognized as sharing a common neuroanatomy and neurobiology.…”
Section: The Drd2 Genementioning
confidence: 99%